Antidysrhythmic drug therapy for the termination of stable, monomorphic ventricular tachycardia: a systematic review. Issue 2 (16th September 2013) - deSouza, Ian S; Martindale, Jennifer L; Sinert, Richard
Abstract : Objective: We performed a systematic review of the literature to compare the efficacy of different drug therapies for the termination of stable, monomorphic ventricular tachycardia (VT). Methods: We searched EMBASE, MEDLINE and Cochrane for trials from 1965 through July 2013 using a search strategy derived from the following clinical question in PICO format: P atients: Adults (≥18 years) with stable monomorphic VT; I ntervention: Intravenous antidysrhythmic drug; C omparator: Intravenous lidocaine or amiodarone; O utcome: Termination of VT. For all drug comparisons, we calculated relative risks (RR; 95% CI) and number needed to treat (NNT, 95% CI) between drugs. We also evaluated the methodological quality of the studies. Results: Our search yielded 219 articles by PubMed and 390 articles by EMBASE. 3 prospective studies (n=93 patients) and 2 retrospective studies (n=173 patients) met our inclusion and exclusion criteria. From the prospective studies, RR of VT termination of procainamide versus lidocaine was 3.7 (1.3–10.5); ajmaline versus lidocaine, RR=5.3 (1.4–20.5); and sotalol versus lidocaine, RR=3.9 (1.3–11.5). From the retrospective studies: procainamide versus lidocaine, RR=2.2 (1.2–4.0); and procainamide versus amiodarone RR=4.3 (0.8–23.6). All 5 reviewed studies had quality issues, including potential bias for randomisation and concealment. Conclusions: Based on limited available evidence from small heterogeneous human studies, for the treatment of stable, monomorphic VT, procainamide, ajmaline and sotalol were all superior to lidocaine; amiodarone was not more effective than procainamide.